(3eNJGQGJ ef GdbUU GdEfLdjRjs - (3GdeGRfj, EHQGgje YHO GdbGOQs; (3aGQhb, YHjQs; (3eQLGf, gHgs ((3GdbGgQIs (3WaQI ddfTQ hGdJhRjYs, 2024)
(3gPG GdcJGH djS eLQO eLehYI bUUjI Hd gh LSQ jUd Hjf GdKbGaGJ jfbd dfG YHQ GdJQLeI GdObjbI hGdGNJjGQ GdeejR ddcGJH EHQGgje YHO GdbGOQ GdeGRfj bUUkG JRNQ HGdYHQ hGdeYGfj, hJfHV HGdMjGI hGdJLOjO, Ef bQGAI gPg GdeNJGQGJ JaJM CeGe GdbGQF fGaPI Ydi Ybhd GdcJGH GdcHGQ eKd JTGQdR OjcfR , GOLGQ BdGf Hh, QhHQJ dhjS, SJjafShf, ChScGQ hGjdO hZjQge hcja GSJWGYhG HegGQJge GdaPI Cf jfbdhG JLGQge hQDGge Edi GdYGdes
Keywords: (3GdCOH GdEfLdjRjs; (3GdeJQLeGJs